American artists in their New York Studios : conversations about the creation of contemporary art - Götz, Stephan; Lue, Robert (Cambridge Stuttgart : Center for Conversation and Technical Studies Harvard University Art Museums Cambridge Daco-Verlag Günter Bläse Stuttgart, 1992)
Baechler, Donald ; Bleckner, Ross ; Burton, Richmond ; Cabrera, David ; Close, Chuck ; David, Michael ; Dryer, Moira ; Dupuis, David ; Evans, Steven ; Gober, Robert ; Jenkins, Michael ; K.O.S. ; Kahn, Tobi ; Kelly, Ellsworth ; Lasker, Jonathan ; Laster, Paul ; Lethbridge, Julian ; Marden, Brice ; McCarty, Marlene ; Rollins, Tim ; Schorr, Collier ; Schuyff, Peter ; Shields, Alan ; Smith, Ray ; Spero, Nancy ; Starn, Doug & Mike ; Wesselmann, Tom
Engels
boek
Keywords: New York; U.S.A.; Verenigde Staten